Future Prospects on Constraining Neutrino Cosmology with the Ali CMB Polarization Telescope - Dongdong Zhang; Jia-Rui Li; Jiaqi Yang; Yufei Zhang; Yi-Fu Cai; Wenjuan Fang; Chang Feng (The Astrophysical Journal, 2023)
We forecast the constraints on the parameters of neutrino physics with the constructions of Cosmic Microwave Background (CMB) temperature, E-mode polarization, and lensing spectra for the ground-based Ali Cosmic Microwave Background Polarization Telescope (AliCPT). To implement the forecast calculations, we perform numerical simulations which show that AliCPT would yield the result σ ( N _eff ) = 0.56 and M _ν < 1.10 eV (95% CL.) with TT, TE, EE, and CMB lensing power spectra for the first year of observation. Moreover, we investigate how the instrumental parameters, such as noise level, FWHM, and sky coverage can affect the constraints on these two parameters. Our forecasting results find that a larger aperture telescope with a larger sky survey strategy would significantly improve the current constraints for AliCPT.